HUBUNGAN INSTAGRAM ADDICTION DENGAN LIFE SATISFACTION PADA EMERGING ADULTHOOD - Aulia, Dini; Lastatia Putri, Bianca; Hasna Vinaya, Nisrina (Psikologi UHAMKA, 2022)
In general, this study aims to see if there is a relationship between Instagram addiction and life satisfaction at the age of emerging adulthood stages. One of the most age ranges of Instagram users is 18-25 years, which is entered into the stage of emerging adulthood. Emerging adulthood is in the mid-stage between late adolescence and early adulthood. Previous research has found that at this stage individuals tend to be faced with higher self-instability than other age groups and find it harder to feel life satisfaction. Life satisfaction itself is influenced by various factors, one of which is related to the use of social media, especially Instagram. It was found that social media users tend to be less satisfied with themselves because they tend to compare themselves to people they see on social media, thus affecting life dissatisfaction in individuals. Participants in the study were 155 respondents aged 18-25 years who used Instagram for at least 3 hours per day. The measuring instruments used are TIAS (The Instagram Addiction Scale) to measure Instagram addiction and SWLS (Satisfaction with Life Scale) to measure life satisfaction. Based on the results of statistical analysis using statistical calculations with the help of Jamovi software application version 1.6 obtained results that there is no significant relationship between Instagram Addiction and Life Satisfaction at the stage of emerging adulthood age that uses Instagram social media with a minimum of 3 hours per day. One factor is that the Instagram Addiction variable requires a diagnosis from the clinical so that it is not only focused on the length of time respondents open Instagram. The results of this study are expected to be used as a reference for providing information related to the importance of understanding Instagram addiction with life satisfaction at the emerging adulthood age stage.